Maharashtra State BoardSSC (English Medium) 7th Standard
Advertisement Remove all ads

Expansion of (a + b)(a - b)

Advertisement Remove all ads

Topics

formula

(a + b)(a - b) = a2 - b2

notes

Expansion of (a + b)(a - b):

(a + b) (a - b) = (a + b) × (a - b)

(a + b) (a - b) = a (a - b) + b (a - b)

(a + b) (a - b) = a2 - ab + ba - b2

(a + b) (a - b) = a2 - b2

∴ (a + b) (a - b) = a2 - b2.

Example

Expand: (3x + 4y)(3x - 4y)

(3x + 4y)(3x - 4y)

= (3x)2 - (4y)2

= 9x2 - 16y2

Example

Expand: 102 x 98

102 x 98

= (100 + 2)(100 - 2)

= (100)2 - (2)2

= 10000 - 4

= 9996.

If you would like to contribute notes or other learning material, please submit them using the button below.

Shaalaa.com | Expansion of (a + b)(a - b)

Shaalaa.com


Next video


Shaalaa.com


Expansion of (a + b)(a - b) [00:02:06]
S
Series: Expansion of (a + b)(a - b)
0%


Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×